MRI-guided core biopsy of the prostate in the supine position - Introduction of a simplified technique using large-bore magnet systems - Schwab, Siegfried; Kuefner, Michael A.; Adamietz, Boris; Engelhard, Karl; Keck, Bastian; Kunath, Frank; Wach, Sven; Wullich, Bernd; Uder, Michael; Engehausen, Dirk (European Radiology, 2013)
Objectives: To introduce a simplified technique for MRI-guided core biopsies (MRGB) of the prostate in the supine position using large-bore magnet systems. Methods: Fifty men with a history of negative transrectal ultrasound-guided biopsies underwent MRGB in either a 1.5-T (13/50) or 3.0-T (37/50) wide-bore MRI unit. MRGBs were conducted with the patients in a supine position using a dedicated MR-compatible biopsy device. Results: We developed a dedicated positioning device for the supine position. Using this device, the biopsies were performed successfully in all patients. Apart from minor rectal bleeding, only one patient developed a major side effect (urosepsis). Histology revealed prostate cancer in 25/50 (50 %) patients. Conclusions: The new technique appears feasible. Its major advantage is the more comfortable and patient-friendly supine position during the biopsy without the need to modify the MRI system's patient table. Key Points: • A novel positioning device for MRI-guided prostate biopsies has been developed. • Biopsies can be performed in the patient-friendly supine position. • The positioning device can be utilised without modifying the MRI's patient table. © 2012 European Society of Radiology.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Biopsy; Magnetic resonance imaging; Prostate cancer; Supine position